2019
DOI: 10.3390/diseases7020040
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Methodology for Evaluating Skin Oxidative Stress Status (SOSS)

Abstract: For the purpose of human disease prevention, several methods have been developed, and are still developing, to assess the oxidative stress status (OSS) of individuals. In the present paper, we describe an approach based on electrochemical detection able to evaluate skin oxidative stress status (SOSS) as a PAOT (Pouvoir AntiOxydant Total)-Skin Score®. Normal reference values for the PAOT-Skin Score® were: 0–62.94 (n = 263). Intra- and inter-assay coefficients of variation were, respectively, 12.47 ± 4.29% and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The determination of the total antioxidant capacity (TAC) has been proposed as a global measure of non-enzymatic antioxidant efficiency despite the problem of inference with uric acid [ 53 , 54 ]. Using an original electrochemical methodology developed by us [ 31 ], we showed that the TAC as evaluated by the PAOT ® score was logically decreased in COVID-19 patients most probably because of their very low levels in vitamin C and GSH. Nevertheless, no correlation could be evidenced between both antioxidants and TAC as also shown in the EPIC Granada–Gipuzkoa study [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the total antioxidant capacity (TAC) has been proposed as a global measure of non-enzymatic antioxidant efficiency despite the problem of inference with uric acid [ 53 , 54 ]. Using an original electrochemical methodology developed by us [ 31 ], we showed that the TAC as evaluated by the PAOT ® score was logically decreased in COVID-19 patients most probably because of their very low levels in vitamin C and GSH. Nevertheless, no correlation could be evidenced between both antioxidants and TAC as also shown in the EPIC Granada–Gipuzkoa study [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…White blood cells and neutrophils were determined by flow fluorocytometry on Sysmex-SN device (Ontario, Canada). The total antioxidant capacity (TAC) of plasma was evaluated by using the PAOT ® (Pouvoir AntiOxydant Total, Institut Européen des Antioxydants, Nancy, France) score as previously described [ 31 ]. Briefly, the measurement was carried out in a reaction medium (1 mL physiological solution at pH ranging from 6.7 to 7.2, temperature 24–27 °C) containing a molecule in a free radical state called mediator (M•).…”
Section: Methodsmentioning
confidence: 99%
“…The determination of the total antioxidant capacity (TAC) has been proposed as a global measure of non-enzymatic antioxidant efficiency despite the problem of inference with uric acid [53,54]. Using an original electrochemical methodology developed by us [31], we showed that the TAC as evaluated by the PAOT ® score was logically decreased in COVID-19 patients most probably because of their very low levels in vitamin C and GSH. Nevertheless, no correlation could be evidenced between both antioxidants and TAC as also shown in the EPIC Granada-Gipuzkoa study [55].…”
Section: Antioxidant Analysismentioning
confidence: 94%
“…An equation is then used to determine the score and determine the overall amount of stress. 48 Recently, a new device was developed by Amorepacific that emits blue light at 456 nm, and can control light intensity and light irradiation time. Additionally, the device can also detect the harmful blue light wavelengths and clinically evaluate blue light blocking performance at those harmful wavelengths.…”
Section: Claim Substantiation Methods For Blue Light Protection Claimsmentioning
confidence: 99%